Hardware and software complex for measuring hard X-ray radiation on the torsatron “Uragan-2M” - Gubarev, S.P.; Klosovsky, A.V.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2021)
This paper presents an automated measuring system for radiation monitoring and measurement of hard X-ray radiation in real time on the “Uragan-2M” torsatron. The system includes an ionizing radiation detector based on a scintillator and a photomultiplier tube, equipment for preliminary processing and normalization of detector signals, and a microcontroller unit for control, measurement and processing.